The Relationship between Three (Human, Perceptual, and Technical) Skills of Financial Managers and Their Effectiveness in Manufacturing Companies with the Intermediate Role of Empowering Managers - Hossein Azimi (Journal of Global Pharma Technology, 2017)
The aim of this study is to investigate the effect of three (human, perceptual, and technical) skills of financial managers on their effectiveness in Gilan province's manufacturing companies with the mediating role of empowering managers. The research method was descriptive-correlational and the statistical population included managers and financial experts of 193 manufacturing companies in Rasht industrial town. Data collection tool was a researcher-made questionnaire which was distributed among 30 active companies by random sampling method. The reliability of the questionnaire was confirmed. Additionally, the content validity of questionnaire was confirmed by the opinion of the experts and its construct validity was confirmed by factor analysis. The results of the correlation test using spss16 software showed that there is a statistically significant effect between the studied variables. Moreover, structural equation modeling and path analysis technique were used to investigate the interactions of research variables. The results obtained from the seven examined hypotheses confirmed the impact of three (human, perceptual, and technical) skills of financial managers on their empowerment in manufacturing companies of Gilan province (P <0.05). Also, the results of this study indicated that the empowerment of managers affects the financial management effectiveness (planning, budgeting, control and assessment) in manufacturing companies of Gilan province (P <0.05).Keywords: Triple skills (Human, Perceptual, and Technical), Effectiveness of managers, Empowerment of managers.